2005
DOI: 10.4049/jimmunol.175.10.6402
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin T1 Expression Is Regulated by Multiple Signaling Pathways and Mechanisms during Activation of Human Peripheral Blood Lymphocytes

Abstract: Stimulation of primary human T lymphocytes results in up-regulation of cyclin T1 expression, which correlates with phosphorylation of the C-terminal domain of RNA polymerase II (RNAP II). Up-regulation of cyclin T1 and concomitant stabilization of cyclin-dependent kinase 9 (CDK9) may facilitate productive replication of HIV in activated T cells. We report that treatment of PBLs with two mitogens, PHA and PMA, results in accumulation of cyclin T1 via distinct mechanisms. PHA induces accumulation of cyclin T1 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 64 publications
3
54
0
Order By: Relevance
“…As the expression of cyclin T1 and CDK9 is low in unstimulated PBLs and increases following mitogenic stimulation, we have suggested that the activity of these complexes might be important for the increased transcriptional needs associated with the process of T cell activation (Marshall et al, 2005). In contrast, in transformed T cells and other cell lines, cyclin T1 levels are comparable to those seen in activated PBLs.…”
Section: Fvp Inhibits Mitogen-induced T Cell Activation In Primary Humentioning
confidence: 84%
See 3 more Smart Citations
“…As the expression of cyclin T1 and CDK9 is low in unstimulated PBLs and increases following mitogenic stimulation, we have suggested that the activity of these complexes might be important for the increased transcriptional needs associated with the process of T cell activation (Marshall et al, 2005). In contrast, in transformed T cells and other cell lines, cyclin T1 levels are comparable to those seen in activated PBLs.…”
Section: Fvp Inhibits Mitogen-induced T Cell Activation In Primary Humentioning
confidence: 84%
“…pCPP-HA-CDK9 and pCPP-HA-dnCDK9 vectors were generated by subcloning EcoRI digested cDNAs into the EcoRI site of the pCPP vector. Lentiviral particles were generated by transient transfection in 293T cells by CaCl 2 method as described in (Marshall et al, 2005) with some significant modifications. Briefly, 15 μg of the transfer vector (directing expression of the gene of interest), 10 μg of pCMVΔ8.2 (packaging construct) and 10 μg of the pCMV-VSV-G (envelope) vector (Sena-Esteves et al, 2004) were cotransfected into 293T cells.…”
Section: Lentiviral Constructs Recombinant Viral Production and Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Hexim1 not only inhibits MHC class II transcription but also is important for the differentiation of neural and hematopoietic cells (24)(25)(26). Because HMBA induces Hexim1 (20,27), it also differentiates a variety of cells (28,29).…”
Section: Discussionmentioning
confidence: 99%